Influence of an abscisic acid (ABA) seed coating on seed germination rate and timing of Bluebunch Wheatgrass. Issue 13 (14th June 2019) - Richardson, William C.; Badrakh, Turmandakh; Roundy, Bruce A.; Aanderud, Zackary T.; Petersen, Steven L.; Allen, Phil S.; Whitaker, Dallin R.; Madsen, Matthew D.
Abstract: Semi‐arid rangeland degradation is a reoccurring issue throughout the world. In the Great Basin of North America, seeds sown in the fall to restore degraded sagebrush ( Artemisia spp.) steppe plant communities may experience high mortality in winter due to exposure of seedlings to freezing temperatures and other stressors. Delaying germination until early spring when conditions are more suitable for growth may increase survival. We evaluated the use of BioNik™ (Valent BioSciences LLC) abscisic acid (ABA) to delay germination of bluebunch wheatgrass ( Pseudoroegneria spicata ). Seed was either left untreated or coated at five separate rates of ABA ranging from 0.25 to 6.0 g 100 g −1 of seed. Seeds were incubated at five separate constant temperatures from 5 to 25°C. From the resultant germination data, we developed quadratic thermal accumulation models for each treatment and applied them to 4 years of historic soil moisture and temperature data across six sagebrush steppe sites to predict germination timing. Total germination percentage remained similar across all temperatures except at 25°C, where high ABA rates had slightly lower values. All ABA doses delayed germination, with the greatest delays at 5–10°C. For example, the time required for 50% of the seeds to germinate at 5°C was increased by 16–46 d, depending on the amount of ABA applied. Seed germination models predicted that the majority of untreated seed would germinate 5–11 weeks after a 15 October simulated planting date. In contrast, seeds treated with ABA were predicted to delay germination to late winter or early spring. These results indicate that ABA coatings may delay germination of fall planted seed until conditions are more suitable for plant survival and growth. Abstract : Wet‐thermal accumulation modeling was used to evaluate the potential of abscisic acid (ABA) as a seed enhancement technology that could delay germination in rangeland settings. Using historical soil moisture and temperature data, it was shown that increasing the level of ABA applied to bluebunch wheatgrass ( Pseudoroegneria spicata (Pursh) Á. Löve) seeds has a positive correlation with germination delay.